Pengaruh Puasa Ramadhan terhadap Kadar Gula Darah pada Pasien Diabetes Mellitus Tipe II (Journal of Telenursing (JOTING), 2019)
This study aims to determine the effect of Ramadan fasting on blood sugar levels in diabetics in Purwakarta City Health Center, West Java. The research design used a quasi-experimental pre and post test with control group. The results of this study using the T-Independent test of fasting differences in blood sugar levels after Ramadan fasting in the control group and the intervention group obtained p value = 0.039